Evidence of Leptospira species and their significance during reintroduction of Eurasian beavers (Castorfiber) to Great Britain. (19th October 2019) - Girling, Simon J; Goodman, Gidona; Burr, Paul; Pizzi, Romain; Naylor, Adam; Cole, Georgina; Brown, Donna; Fraser, Mary; Rosell, Frank Narve; Schwab, Gerhard; Elliott, Mark; Campbell‐Palmer, Roisin
Abstract : The Scottish Beaver Trial (SBT) reintroduced the Eurasian beaver ( Castor fiber ) in 2009 using wild‐caught Norwegian beavers. This included a six‐month prerelease quarantine in Devon, England. The International Union for Conservation of Nature (IUCN) and government guidelines for health screening were followed, including testing for Leptospira species. Unlicensed beavers, from Germany, were also identified in Scotland (Tayside) and Devon (later forming the River Otter Beaver Trial (ROBT)) and were health‐screened under licence. Due to positive Leptospira species results and lack of prerelease screening in ROBT and Tayside, beavers from Germany and Norway (range sources) were screened. One hundred and fifty‐six samples from 151 beavers were analysed by Leptospira species quantitative PCR (qPCR) (n=73 kidney (postmortem)/urine samples (antemortem)) or microscopic agglutination test (MAT, Leptospira pools 1–6) (n=83 serum samples). No beavers from Norway (95 per cent confidence interval (CI) 0–5.6 per cent, n=52), Tayside or SBT postrelease (95 per cent CI 0–4.6 per cent, n=63) tested positive. Seven beavers from Germany and Devon were positive. This gives an overall 9.3 per cent (95 per cent CI 5.2‐15.1 per cent) exposure level, of which 4.6 per cent (95 per cent CI 1.9‐9.3 per cent) suggested infection on a positive qPCR (n=1) or MAT titre of at least 1/400 (n=6), although none had abnormal physical, biochemical or haematological changes. This study suggests that Leptospira species infection in wild Eurasian beavers occurs at a low level, has no sex bias and does not appear to cause significant morbidity or mortality.